Pembentukan Personal Branding Rachel Vennya sebagai Influencer dan Entrepreneur di Media Instagram - Ananda, Rizki Ayu; Matondang, Muhammad Alfikri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Personal branding is the process of creating and managing an image or reputation to gain the trust of others and make yourself known. Rachel Vennya, an influencer and entrepreneur, uses Instagram as a forum to build a personal brand. The study aims to study how Rachel Vennya's personal branding as an influencer and entrepreneur grows in Instagram media. In terms of personal branding, Rachel Vennya is known as an innovative and creative person. He keeps moving forward in various fields because of his creative talents. Rachel used Instagram as a place to build her personal branding as an influencer and entrepreneur by implementing eight concepts of personalized branding. Rachel used her Instagram account under her username @rachelvennya to post photos and videos related to her work as an influencer and her business activities. He also posted stories about his personal life, family, friends, co-workers, and community members.